2023
DOI: 10.3390/molecules28176203
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical and Antioxidant Activity of Compounds Containing 1,3-Dicarbonyl Moiety: An Overview

Laima Bērziņa,
Inese Mieriņa

Abstract: Free radicals and oxidants may cause various damages both to the lifeworld and different products. A typical solution for the prophylaxis of oxidation-caused conditions is the usage of various antioxidants. Among them, various classes are found—polyphenols, conjugated polyalkenes, and some sulfur and nitrogen derivatives. Regarding the active site in the molecules, a widely discussed group of compounds are 1,3-dicarbonyl compounds. Among them are natural (e.g., curcumin and pulvinic acids) and synthetic (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 201 publications
(227 reference statements)
0
9
0
Order By: Relevance
“…Results on IC 50 showed that, C. maxima leaf supplemented diet demonstrated antiradical activity. Increasing antiradical activity is indicated by the smaller IC 50 value 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Results on IC 50 showed that, C. maxima leaf supplemented diet demonstrated antiradical activity. Increasing antiradical activity is indicated by the smaller IC 50 value 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies also have suggested that curcumin can support collagen production, skin health, and appearance. It contains phenolic and β-diketone functional groups that contribute to its antioxidant activity ( Bērziņa and Mieriņa, 2023 ), which is a major contributor to skin aging. By scavenging free radicals and mitigating oxidative damage Curcumin can reduce signs of aging such as wrinkles and age spots ( Jiang et al, 2020 , Elkhateeb et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin and its analogs, d methoxycurcumin (II) and bisdemethoxycurcumin (III), also present in C. longa rhizom are commonly referred to as curcuminoids [2]. Besides being used as a supplement, seasoning, food preservative, flavoring, and coloring in the food industry [3], curcumin has various biological and pharmacological activities, including antioxidant [4], anti-inflammatory [5], antimicrobial [6], anticancer [7], and antiparasitic [8] actions. However, limitations have prevented it from being approved as a therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%